Long-term operational strategy of microalgal-bacterial granular sludge towards strengthened sulfadiazine antimicrobial resistance control - Lin, Shupeng; Pan, Minmin; Ma, Yanfang; Chen, Zhihao; Lyu, Tao; Dong, Renjie; Ruan, Roger; Liu, Shan (Elsevier, 2026)
Harnessing the dynamic interactions within the microalgal-bacterial granular sludge (MBGS) systems represents an emerging biotechnological frontier in tackling antibiotic pollution. Nevertheless, effective long-term treatment targeting strengthened antimicrobial resistance remains challenging. This study explored the operational strategies of pre-accumulation with antibiotic-free cultivation and pre-acclimatization with 5 mg/L sulfadiazine (SDZ) exposure for long-term, effective high-concentration SDZ removal (stepwise increase up to 50 mg/L), while controlling antibiotic resistance genes. The results showed that pre-accumulation achieved a stable microbial structure and greater antibiotic removal (up to 99.9 %) under extremely high SDZ concentration (50 mg/L) compared to pre-acclimatization, while pre-acclimatization suffered more oxidative damage, leading to lower biomass and pigments accumulation, but higher SDZ removal under 30 mg/L. The amide bond hydrolysis was identified as the predominant degradation pathway, resulting in less toxic by-products. Pre-accumulation performed better in controlling relative abundance of target sulfonamide antibiotic resistance genes (ARGs, sul1 and sul2) compared to pre-acclimatization. Genes encoding metabolic pathways related to antibiotic removal remained active, with downregulated genes encoding growth. Chlorella exhibited a protective effect on bacteria and inhibited ARGs spread, whereas Nakamurella and Nitrosomonas might be the key bacteria in SDZ biodegradation, but also served as potential hosts of ARGs. The continuous and efficient removal of SDZ, along with the mitigation of ARGs spread and toxic by-product accumulation under ultra-high antibiotic exposure, can be attributed to the MBGS system's initial operational strategy. The initial operational strategy involving stress pre-acclimation and biomass pre-accumulation offers a robust and adaptable solution for treating antibiotic-containing wastewater.
Keywords: 40 Engineering; 4105 Pollution and Contamination; Antimicrobial Resistance; Emerging Infectious Diseases; Infectious Diseases; Biodefense; Infection; Strategic, Defence & Security Studies; 34 Chemical sciences; 41 Environmental sciences